Endoscopic sphincteroplasty: An effective method of extracting bile duct stones by ERCP patients with Billroth II gastrectomy - , Orhan SEZGİN, Uğur YILMAZ, Fikret DEMİRCİ, Burhan ŞAHİN (Turkish Journal of Gastroenterology 1, 2019)
-